2006
DOI: 10.1128/mcb.00383-06
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin Activates AMP-Activated Protein Kinase in Endothelial Cells via a Pathway Involving Ca2+/Calmodulin-Dependent Protein Kinase Kinase β

Abstract: AMP-activated protein kinase (AMPK) is a sensor of cellular energy state in response to metabolic stress and other regulatory signals. AMPK is controlled by upstream kinases which have recently been identified as LKB1 or Ca2؉ /calmodulin-dependent protein kinase kinase ␤ (CaMKK␤). Our study of human endothelial cells shows that AMPK is activated by thrombin through a Ca 2؉ -dependent mechanism involving the thrombin receptor protease-activated receptor 1 and G q -protein-mediated phospholipase C activation. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
169
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(178 citation statements)
references
References 50 publications
(101 reference statements)
9
169
0
Order By: Relevance
“…It is known that Ca 2ϩ entry signaling activates CaMKK␤ to induce AMPK␣ phosphorylation in endothelial cells (15,22). In this study, we observed that pretreatment with CaMKK␤ inhibitor STO-609 suppressed thrombin-induced AMPK␣1 phosphorylation indicating that CaMKK␤ is essential to activate AMPK␣1 in endothelial cells.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…It is known that Ca 2ϩ entry signaling activates CaMKK␤ to induce AMPK␣ phosphorylation in endothelial cells (15,22). In this study, we observed that pretreatment with CaMKK␤ inhibitor STO-609 suppressed thrombin-induced AMPK␣1 phosphorylation indicating that CaMKK␤ is essential to activate AMPK␣1 in endothelial cells.…”
Section: Discussionsupporting
confidence: 54%
“…The upstream-activating enzyme AMPK kinase or the closely related tumor suppressor kinase LKB1 can phosphorylate the catalytic ␣-subunit of AMPK in an AMP-dependent manner (23,34). AMPK can also be activated in an AMP-independent manner, which involves CaMKK␤ (22,23). An increase in intracellular Ca 2ϩ is required for CaMKK␤ activation (22).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The CaMKKs are expressed at highest levels in neural tissue [19], and the distribution of this Ca 2+ -mediated pathway for AMPK activation in other cell types is still being investigated. It clearly occurs in neurones in response to activation of voltage-gated Ca 2+ channels [16], in T lymphocytes in response to stimulation of the antigen receptor [20], and in endothelial cells in response to activation of the thrombin receptor, which is coupled via Gq to release of inositol trisphosphate and hence of Ca 2+ from the endoplasmic reticulum [21].…”
Section: Mammalian Ampk -Regulation By Amp/atp and Upstream Kinasesmentioning
confidence: 99%